Effect of Phosphate Starvation on Gene Expression in Komagataella phaffii Cells - Valeria V. Ishtuganova; Anton V. Sidorin; Anastasiya S. Makeeva; Marina V. Padkina; Andrey M. Rumyantsev (Microorganisms)
Phosphorus is a key nutrient for all organisms. The study of phosphate metabolism and its regulation is important for understanding the evolutionary processes of regulatory systems in eukaryotic cells. The methylotrophic yeast Komagataella phaffii is an efficient producer organism, and it is actively used in biotechnological production. The high practical importance of K. phaffii has stimulated active research to find new tools to work with this yeast and optimize its cultivation conditions. In this work, we observed the effect of phosphate starvation on gene expression in K. phaffii at the transcriptome level. Phosphate starvation had a significant effect on general cell metabolism. K. phaffii cells demonstrated a response to this macronutrient deficiency through an altered gene expression of carbon and amino acid metabolism. We observed the activation of phosphate and polyphosphate metabolism gene expression. In this case, there was a suppression of ribosome biogenesis genes and genes involved in fatty acid beta-oxidation and translation processes.